2013
DOI: 10.1111/pde.12143
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report on Autosomal Recessive Total Congenital Anonychia

Abstract: A 21-year-old woman presented with a history of the absence of the nails of all her fingers and toes since birth. Her grandfathers were first degree relatives. Her two brothers (26 and 28 years old) had the same anomalies. Autosomal recessive inheritance of this disease was supported in our cases because the parents were consanguineous and the disease occurred in two brothers and a sister.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Fully developed supernumerary digits develop nails. It is known that a bone core has to be present at the distal phalanx for the development of a nail anlage; atelephalangia is associated with lack of nail formation or nail hypoplasia [4,5], although total complete anonychia also occurs without bone changes [6]. Whether or not an additional bone core, which may be found in the bifid tip of the distal phalanx of the little toe, is sufficient to induce an accessory nail remains a matter of speculation at this moment.…”
Section: Discussionmentioning
confidence: 99%
“…Fully developed supernumerary digits develop nails. It is known that a bone core has to be present at the distal phalanx for the development of a nail anlage; atelephalangia is associated with lack of nail formation or nail hypoplasia [4,5], although total complete anonychia also occurs without bone changes [6]. Whether or not an additional bone core, which may be found in the bifid tip of the distal phalanx of the little toe, is sufficient to induce an accessory nail remains a matter of speculation at this moment.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that a bone core has to be present at the distal phalanx for the development of a nail anlage. Atelephalangia is associated with lack of nail formation or nail hypoplasia [ [4] , [5] ], although total or complete anonychia also occurs without bone changes [ 6 ]. On the other hand, nail epithelium also has a special role in bone formation and digit regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Previous report [1], had indicated that it could be found in countries such as, Russia, Great Britain, America, Holland, Iran. Recently, it has been reported in Brazil [2] and Turkey [3]. In this manuscript, we use a Saudi family as a case study.…”
Section: Introductionmentioning
confidence: 99%